Study of the formation mechanism of bundle structures using AFM tip-based nanoscratching approach. (February 2020) - Wang, Jiqiang; Yan, Yongda; Chang, Shunyu; Wang, Tong; Geng, Yanquan; Gan, Yang
Abstract: To investigate the formation mechanism of bundle structures on polycarbonate (PC) surfaces, atomic force microscopy (AFM) was utilized to scratch a PC sheet. A theoretical model for the AFM tip, which accounted for the friction force exerted on the probe, was established to illustrate the torsion angle of the tip. The formation of bundle structures was determined by a critical friction force, and a stick-slip process was used to explain the formation mechanism. The influence of the scratching parameters, including the scratching angles, normal loads, velocities, and feed values, on the amplitude and wavelength of the bundle structures was studied. These results can provide guidance for the fabrication of higher quality bundle structures on a polymer sample surface. Highlights: A theoretical model for the AFM tip accounted for the friction force exerted on the probe was established. The bundles were formed with a critical friction force and the formation mechanism was proved as the stick-slip process. The relationships between the machining parameters and the feature sizes of the obtained nanobundle structures were studied.